Acute Aneurysmal Subarachnoid Haemorrhage following Coital Headache successfully treated with Endovascular Flow Diversion - Chatterjee, Apratim; Mahajan, Anshu; Goel, Gaurav; Ojha, Piyush (Nepal Journal of Neuroscience, 2021)
Headache associated with sexual activity is a difficult diagnosis for physicians and sometimes underlies grave etiologies. One such cause associated with high morbidity and mortality is subarachnoid hemorrhage due to aneurysm rupture. This is a case of a 39 year old male, presenting with coital headache for few episodes. CT showed subarachnoid hemorrhage, Fischer Grade 3. Digital subtraction angiography revealed Right Internal carotid artery very small aneurysm which was endovascularly managed with FRED (flow-redirection endoluminal device, Microvention, Aliso Viejo, California, USA) flow diverter placement across the aneurysm. Follow up revealed complete resolution of aneurysm with no residual clinical symptoms. The following case reveals the importance of identifying sexual headache as a presenting symptom of grave etiology like aneurysmal rupture and its early diagnosis and management to avoid mortality.